Kajian aktivitas antioksidan pada isolat akar dan buah palem merah (Cyrtostachys renda Blume) dengan metode DPPH - Syamsurizal, Syamsurizal; Pratiwi, Puspa Dwi; Novia, Ria; Sitanggang, Sarah Dianora; Rani, Amalia; Damayani, Mira Ovita (Journal of Pharmaceutical and Sciences, 2023)
Free radical reactions were increased in cells, leading to degenerative illnesses. Antioxidant components may inhibit free radical reactions. Exogenous antioxidants are primarily found in red palm (Cyrtostachys renda Blume). This study aimed to assess the potency of antioxidant activities of fruit and root C. renda, which were extracted in n-hexane, ethyl acetate, dichloromethane, and water. The bioactivity of the fractionate, isolate, and positive control (ɑ-tocopherol) were used in the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The result showed that the ethyl acetate extract of fruit and roots had the highest antioxidant activity, with an IC50 value of 11.47 ± 0.169 µg/mL (very strong category) in the roots. In contrast, the IC50 value in the fruit was 10.69±0.084 g/mL. Further evaluating of antioxidant activity in the roots revealed that the IC50 value for isolate A was 28.17±0.232, while the IC50 value for isolate B was 24.80±0.296 g/mL. The fruit of isolation C had an IC50 value of 14.91±0.247 g/mL, while isolate D had an IC50 value of 25.98±0.133 g/mL. Compared to the antioxidant activity of ɑ-tocopherol, which has an IC50 value of 13.54±0.038, isolate C is very potent inhibit free radical scavenger. In contrast, the other isolates are two times lower than the positive control.